Covid-19 Pandemic and School Dropout Rates: Empirical Evidence from Indonesia - Ibnu Syukron Halid (Journal of Economics Research and Social Sciences, 2022)
The Covid-19 pandemic has disrupted all aspects of life, including the education aspect. The government then tackled the virus's transmission rate by issuing a policy to stop face-to-face learning activities and replace them with online learning activities. However, the inequality of information technology facilities has made it difficult for several regions in Indonesia to teach online. It more or less impacts the dropout rate, especially at the elementary school level. This study then aims to determine how much the Covid-19 pandemic affects the dropout rate in Indonesia at the elementary school level by considering other factors such as school facilities and infrastructure, children's academic abilities, and economic control variables. So far, no similar study discusses the pandemic's impact on the dropout rate measured quantitatively, especially in Indonesia. This study uses panel data analysis from 34 provinces in Indonesia from 2017 to 2021. The results indicate that the Covid-19 pandemic is associated with the dropout rate increasing at the primary school level by 36.4%.